Simulasi Pengembangan Pembelajaran dengan Pemanfaatan Kecerdasan Buatan (AI) Bagi Guru di SMP Negeri 1 Kota Ambon - Lasaiba, Mohammad Amin; Tetelepta, Edward Gland; Asep, Asep; Partini, Dwi; Manakane, Susan Evelin (Universitas Pattimura, 2024)
The use of artificial intelligence (AI) technology in education offers significant potential for enhancing the quality of learning and teaching efficiency. This study aims to evaluate AI-based teaching material development training using Kelas Ajaib on the Canva application, provided to 40 teachers at SMP Negeri 1 Ambon. The methods used included a workshop approach and interactive simulations, designed to improve teachers' competence in designing technology-based teaching media. The evaluation results showed that participants' enthusiasm reached 85%, while satisfaction levels were 86%, indicating a positive response to the training. However, competence levels in developing teaching media only reached 75%, indicating the need for additional mentoring and improved technological infrastructure. The main obstacles identified included hardware limitations and adaptation to new technology. Recommendations include further training, increased technical support, and the strengthening of school infrastructure. The implications of this training highlight the importance of collaboration among educational stakeholders to ensure the sustainability and effectiveness of AI technology implementation in teaching. Further research is recommended to evaluate the long-term impact of this training on teaching quality and student engagement.